IMPLEMENTATION OF THREE WINNING FORMULA: INTEGRATED EDUCATION MANAGEMENT MODEL AT PPTQ IBNU ABBAS KLATEN - Kusyaeni, Kusyaeni; Retnaningsih, Woro; Nashirudin, Muh; Wardiyono, Kelik (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to describe the implementation of the Three Winning Formula as an integrated education management model at SMAIT Ibnu Abbas Klaten. This study uses a qualitative descriptive approach with data collection through interviews, observations and document studies. Data analysis is carried out through data reduction and checking the validity of data using data triangulation. The results of this study indicate that the integrated education management model 'Three Winning Formula' at SMAIT Ibnu Abbas Klaten is implemented through a structured cycle involving three synergistic units and comprehensive evaluation across all pillars; spiritual, intellectual and managerial. Strengthening aspects of worship, faith and spiritual discipline (for example: congregational prayer, tilawah coaching, dhikr, and Islamic manners). Important findings from research on the Three Winning Formula (Excellent Academics, Tahfidz and Morals, and governance (Good Governance) show that the synergistic integration of the three is the foundation of a strategy in forming an Islamic educational institution that is superior, has character, and is sustainable in the modern era.